2017
DOI: 10.21767/2573-0320.100010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health-Seeking Behavior: HIV Test Experiences among Youth Aged 15-24 Years in Cameroon and Gabon

Abstract: Background: HIV testing plays a vital role in the prevention and reduction of the HIV epidemic and is a crucial measure for HIV prevention programs and services. However, reports from Cameroon and Gabon indicated low HIV testing and lack information about the predicting factors of HIV testing. Therefore, the aims of this study were to investigate the HIV testing experiences and to explore its predicting factors among 15-24 aged Cameroonian and Gabonese youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
(97 reference statements)
1
4
1
Order By: Relevance
“…HIV knowledge is also a predisposing factor derived from the Anderson's Behavioral Model used in our study. In this study, youth with adequate HIV knowledge had higher testing odds than previous studies [14,19,25,52]. Respondents who had adequate HIV knowledge that a healthy person can get HIV and a person get HIV by sharing food with an infected person were 1.22 and 1.26-times more likely to have been tested for HIV than those without adequate HIV knowledge.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…HIV knowledge is also a predisposing factor derived from the Anderson's Behavioral Model used in our study. In this study, youth with adequate HIV knowledge had higher testing odds than previous studies [14,19,25,52]. Respondents who had adequate HIV knowledge that a healthy person can get HIV and a person get HIV by sharing food with an infected person were 1.22 and 1.26-times more likely to have been tested for HIV than those without adequate HIV knowledge.…”
Section: Discussioncontrasting
confidence: 52%
“…Age has a significant association with testing among youth in SSA, and HIV testing was lower in adolescents (15~19 years) than those aged 20~24 [11][12][13]. Marital status and gender showed an association with HIV testing [14][15][16][17][18]. The odds of testing were higher among married youth compared to single youth [11,16].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…About 33% of all new HIV infections in Kenya in 2017 occurred among adolescents and young people aged 15-24 years (NASCOP, 2018). This report is supported by the studies conducted by Abiodun et al, (2014); Chimoyi et al, (2015); Hadish et al, (2017), suggested that older individuals are more likely to use HIV Counselling and Testing (HCT) services as opposed to the younger ones. It might be that older people perceive themselves to be at high risk of acquiring HIV virus and will therefore readily access HCT service.…”
Section: Introductionsupporting
confidence: 69%
“…It might be that older people perceive themselves to be at high risk of acquiring HIV virus and will therefore readily access HCT service. However, with advancing age, individuals may also become more educated hence increasing the awareness and economic stability to go for HIV testing (Hadish et al, 2017). This is a challenge for the Kenyan youth population as they are at high risk of contracting HIV infection and hence the need to scale up HCT uptake initiatives.…”
Section: Introductionmentioning
confidence: 99%